The national margin of appreciation and the content of freedom of thought, conscience and religion in the European Convention on Human Rights - Fernández Parra, Sergio Alejandro (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This paper will study the figure of the national margin of appreciation and its application by the European Court of Human Rights. The purpose of this study is to show that the frequent use of this figure prevents a uniform interpretation of the right to freedom of thought, conscience and religion in the European System of Human Rights. To test this hypothesis, the aforementioned figure will be compared with the control of conventionality and the way in which the latter figure has been applied by the Inter-American Court of Human Rights. The latter in order to highlight the interpretative and protection flaws of the rights generated by the use of the national margin of appreciation.